A facile and efficient method for the synthesis of N-substituted isoindolin-1-one derivatives under Pd(OAc)2/HCOOH system. Issue 23 (7th June 2017) - Zhou, Yang; Chen, Ping; Lv, Xue; Niu, Junxing; Wang, Yingying; Lei, Min; Hu, Lihong
Graphical abstract: Highlights: The isoindolin-1-ones are synthesized from 2-formylbenzoic acid and amine under Pd(OAc)2 /HCOOH system. This procedure is green, efficient, and high yields. This method is also suitable for the modification of natural products. Abstract: A facile and efficient method for the synthesis of N -substituted isoindolin-1-one derivatives from 2-formylbenzoic acid and amine under Pd(OAc)2 /HCOOH system has been described. The whole process is carried out in ligand-free conditions and furnished the desired products by reductive intramolecular cyclization. Furthermore, this procedure is applied successfully for the modification of natural products, such as vindoline and estrone.